Normative Review of Legal Liability for Notaries or Officials of Land Deed Makers in Falsification of Land Rights Transfer (Case Study of Land Transfer Rights Belonging to the Actress Nirina Zubir Family) - su beto; Pieter Latumeten (IHSA Institute, 2022)
The legal fact of the Nirina Zubir case is that there was a transfer of land rights belonging to her mother by her household assistant. The process of transferring rights which was allegedly carried out by elements of the land mafia made researchers interested in studying more deeply. The involvement of the land deed maker/notary in this case is because the perpetrator changes the name of the deed and sells the deed by buying and selling with a sale and purchase deed made before the PPAT. The existence of a Notary/Official Making Land Deed is very important in order to create legal certainty over land rights owned. In carrying out the functions and positions of a notary, it is regulated in the notary code of ethics in accordance with applicable laws. This research uses normative research methods. The data used are primary data and secondary data. Notary/Land Deed Making Official who makes an authentic deed on land with a process that is not in accordance with applicable regulations and has the potential to harm other parties may be subject to sanctions in the form of administrative sanctions, civil sanctions and criminal sanctions. The imposition of sanctions on the Notary/PPAT is expected so that in carrying out his work the Notary/PPAT must be more careful and thorough so as not to harm the parties with an interest in the deed.